PELAKSANAANBERNYANYI SECARA UNISONO PADA PEMBELAJARAN SENI BUDAYA DI KELAS VII A SMP NEGERI 1 SITIUNG - Prihandono, Eko; Yensharti, Yensharti (SENDRATASIK UNP, 2019)
Abstract This research aims to determine the implementation of cultural arts learning activities in VII-A class in SMP Negeri 1 Sitiung whether in accordance with the prevailing curriculum. This type of research is qualitative research with a descriptive method. The main instrument in this research is its own researchers. Data collection techniques are conducted by way of library studies, observations, interviews and documentation. The steps for analyzing data are studying all data, reducing data, presenting data. The results showed that the implementation of learning in SMPN Negeri 1 Sitiung has not used any interesting media. While in the Learning Implementation Plan (RPP) lead students to hear directly the songs that will be learned using electronic media. The teacher looks stammering read the song notation. Some Siswa–siswi class VII A SMPN Negeri 1 Sitiung still do not possess several indicators of learning objectives and do not understand the technique of singing well, it can be seen when students sing the song in the class. So in school should students also learn and practice Unisono singing at home, in order to get maximum results and objectives achieved. Keywords: Implementation of singing, Unisono, cultural arts